Issues and challenges in courseware development : a project managers perspective. - Chow, Mee Ling; Yap, Ngee Thai; Chan, Mei Yuit (2008)
Many educational institutes venturing into courseware development to create online learning materials for their own students are often not aware of the challenges that lie ahead in managing courseware development projects. This paper highlights the potential challenges a courseware development project may face. It discusses lessons learnt from development projects carried out in Malaysia for content and language-based courses. Particularly, real cases will be presented to highlight challenges and the steps that were taken to overcome them within the constraints of time, budget, curriculum demands, client expectations, and competencies of content providers.